2012
DOI: 10.1111/j.1398-9995.2011.02784.x
|View full text |Cite
|
Sign up to set email alerts
|

EAACI consensus statement for investigation of work‐related asthma in non‐specialized centres

Abstract: Work-related asthma (WRA) is a relevant problem in several countries, is cause of disability and socioeconomic consequences for both the patient and the society and is probably still underdiagnosed. A correct diagnosis is extremely important to reduce or limit the consequences of the disease. This consensus document was prepared by a EAACI Task Force consisting of an expert panel of allergologists, pneumologists and occupational physicians from different European countries. This document is not intended to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 100 publications
1
57
0
3
Order By: Relevance
“…Similarly, exhaled NO measurement during work and rest periods, as the analysis of induced sputum, help improving the accuracy of the diagnosis of occupational asthma [82]. The European Academy of Allergology and Clinical Immunology specifies that the exhaled NO measurement, less specific than the cell count in induced sputum, provides useful information when its analysis is not possible, which is the case in routine practice [83].…”
Section: Contribution Of Exhaled No Measurement In Occupational Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, exhaled NO measurement during work and rest periods, as the analysis of induced sputum, help improving the accuracy of the diagnosis of occupational asthma [82]. The European Academy of Allergology and Clinical Immunology specifies that the exhaled NO measurement, less specific than the cell count in induced sputum, provides useful information when its analysis is not possible, which is the case in routine practice [83].…”
Section: Contribution Of Exhaled No Measurement In Occupational Asthmamentioning
confidence: 99%
“…De même, la mesure du NO expiré pendant des périodes de travail et de repos, comme l'analyse de l'expectoration induite, permet d'augmenter la précision du diagnostic d'asthme professionnel[82]. L'Académie européenne d'allergologie et d'immunologie clinique précise que la mesure du NO expiré, moins spécifique que le compte des cellules dans l'expectoration induite, apporte des informations utiles quand l'analyse de celle-ci n'est pas possible, ce qui est le cas en pratique quotidienne[83]. En résumé, la mesure du NO expiré ne peut remplacer les explorations de référence de l'asthme professionnel mais peut contribuer au diagnostic, au même titre que des résultats obtenus par d'autres techniques non ou peu invasives comme l'expectoration induite ou les condensats de l'air exhalé[84].Données médico-économiquesLa mesure du NO expiré pour détecter l'inflammation dans l'asthme est actuellement remboursée dans plusieurs pays d'Europe (Suisse, Pays-Bas, Danemark, Norvège, Italie, Portugal, République Tchèque).…”
unclassified
“…WRA encompasses both occupational asthma (OA), defined as 'asthma caused by the workplace' and 'work-exacerbated asthma' (WEA), occurring in patients with pre-existing or concurrent asthma and exacerbated by different work-related factors (i.e. aeroallergens, exercise, irritants) (154). OA can be further divided into two subtypes: an allergic form (90% of all OA) (155), caused by both an IgE-mediated mechanism towards high (HMW) and low (LMW) molecular weight agents (106), and a non-IgEmediated form (nonallergic, irritant-induced [occupational] asthma (IIOA)), towards specific LMW agents in which the mechanism has not been characterized yet.…”
Section: Occupational/work Relatedmentioning
confidence: 99%
“…This review refers to studies that reported new causes of well documented IOA or to studies reporting known causes of IOA encountered in new occupational environmental conditions. However, the level of evidence for causation varied between the studies [7][8][9], specific inhalation challenges (SICs) being considered the reference standard.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of IOA first relies on a good history with the demonstration that asthma is caused by work exposure, ideally with identification of the responsible agent [1,7,8]. However, the latter may not always be possible and workers might be exposed to several sensitizers at work.…”
Section: New Agentsmentioning
confidence: 99%